School Spread and Principalsâ€™ Administrative Competence of Secondary Schools in Edo and Kwara States, Nigeria - Tijani, Abdulganiy Adebayo; Fasasi, Y. A. (NIU Journal of Social Sciences, 2018)
This paper examined the spread of public secondary schools and investigated the significance difference between principalsâ€™ administrative competence in Edo and Kwara States. Descriptive research design was adopted for the study. The population comprised 417 and 305 principals of public secondary schools in Edo and Kwara States  respectively. A sample of 100 schools were selected from Edo State and 60 Schools in Kwara State. Stratified random sampling technique was adopted for selecting the sample. The stratification was based on three senatorial districts in the two states. 350 respondents were selected using simple random sampling method. This comprised of 200 and 150 respondents from Edo and Kwara States respectively. Two instruments taggedâ€Principals Administrative Questionnaire (PAQ)â€ and profoma titled â€œSchool Spread Profoma (SSP)â€ were used to collect relevant data. The PAQ was validated by four experts from Department of Educational Management. The reliability co-efficient of 0.70 was obtained through test re-test method using Pearson product moment correlation statistic. The findings of the study revealed that spread of schools in Edo and Kwara States were not based on population of the community. The principals administrative competence in the two states were moderate. Also, there was no significant different between Principals administrative competence in Edo and Kwara States owned secondary schools. The paper recommends even spread of schools in the states based on students and community population. Also, there is need for improvement on principalsâ€™ administrative performance through workshop, conference so as to enhance studentsâ€™ academic performance.